MRI criteria for the diagnosis of multiple sclerosis: MAGNIMS consensus guidelines. Issue 3 (March 2016) - Filippi, Massimo; Rocca, Maria A; Ciccarelli, Olga; De Stefano, Nicola; Evangelou, Nikos; Kappos, Ludwig; Rovira, Alex; Sastre-Garriga, Jaume; Tintorè, Mar; Frederiksen, Jette L; Gasperini, Claudio; Palace, Jacqueline; et al.
Summary: In patients presenting with a clinically isolated syndrome, MRI can support and substitute clinical information in the diagnosis of multiple sclerosis by showing disease dissemination in space and time and by helping to exclude disorders that can mimic multiple sclerosis. MRI criteria were first included in the diagnostic work-up for multiple sclerosis in 2001, and since then several modifications to the criteria have been proposed in an attempt to simplify lesion-count models for showing disease dissemination in space, change the timing of MRI scanning to show dissemination in time, and increase the value of spinal cord imaging. Since the last update of these criteria, new data on the use of MRI to establish dissemination in space and time have become available, and MRI technology has improved. State-of-the-art MRI findings in these patients were discussed in a MAGNIMS workshop, the goal of which was to provide an evidence-based and expert-opinion consensus on proposed modifications to MRI criteria for the diagnosis of multiple sclerosis.